- #1

- 5

- 0

you guys dont hv 2 solve the question for me, just guide me to the answer

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter helmi
- Start date

- #1

- 5

- 0

you guys dont hv 2 solve the question for me, just guide me to the answer

- #2

arildno

Science Advisor

Homework Helper

Gold Member

Dearly Missed

- 10,025

- 134

Convert one logarithm into its equivalent logarithm expression for the other base.

To do so, the general picture is that for positive number a,b,c, we have:

[tex]c=a^{\log_{a}(c)}=b^{\log_{b}(c)}[/tex]

Taking the a-logarithm of the middle and last expression, we have:

[tex]\log_{a}(c)\log_{a}(a)=\log_{b}(c)\log_{a}(b)[/tex]

That is:

[tex]\log_{b}(c)=\frac{\log_{a}(c)}{\log_{a}(b)}[/tex]

- #3

- 5

- 0

(log3 2x)/(log3 2) - log3 (3x-1) = 2

1.585(log3 2x) -log3 (3x-1) = 2

log3 (2x)^1.585 - log3 (3x-1) = 2

log3 ( (2x^1.585)/(3x-1) ) = 2 , is this correct? then what?

- #4

- 5

- 0

Share: